Preservation and evaluation of spiced chayote juice using hurdle technology - Sangma,Chesi (2019)
Abstract Chayote (Sechium edule) is a perennial climbing plant, belonging to the Cucurbitaceae family and is neglected or underutilized as a food or as a raw material in the food industry because of its bland taste. This bland taste can be overcome by blending with a suitable substrate such as sugarcane juice along with natural flavouring. However, this blending represents a preservation problem for the spiced juice, since both chayote juice and sugarcane juice are prone to microbial attack. Therefore, an attempt was made in the present study to preserve the spiced chayote juice by employing different hurdles i.e. pasteurization temperature (70 °C and 80 °C) and pasteurization time (10 and 20 min) followed by the addition of different concentrations of potassium metabisulphite (KMS) (200, 300 and 400 ppm). The samples so prepared were filled into glass bottles and stored under refrigeration for forty-five days. As the storage period proceeded there were significant decreases in pH, total protein content, total phenolic compounds, antioxidant activity, reducing power, metal chelation, tannin content, ascorbic acid content and overall acceptability, whereas there were significant increases in TSS (total soluble solids), titratable acidity, reducing sugars, total sugar, TPC (total plate count) and MIC (minimum inhibitory concentration). A cluster analysis of the data revealed that the pasteurization temperature exerted the most significant effect on the physicochemical and sensory characteristics of the spiced chayote juice as compared to the pasteurization time and KMS concentration, which failed to fall into the separate and respective clusters. In a nutshell, it was concluded that spiced chayote juice can be successfully preserved using hurdle technology (pasteurizing at 70 °C for 10 min followed by the addition of 400ppm KMS).